Alpha-l-Protease Inhibitor, an Acute Phase Reactant in Inflammation - Lamontagne, Raoul Louis (My University, 1982)
Alpha-l-protease inhibitor (αlPi) is a plasma glycoprotein which plays a major role in limiting proteolysis during inflammation due to its broad spectrum of inhibitory activity.
The purification and partial characterization of αlPi have allowed for its investigation as an acute phase reactant during inflammation.
Mouse αlPi is a glycoprotein of molecular weight 53,500 with a half-life of approximately 15.5 hours. On two dimensional immunoelectrophoresis, two variants of αlPi were seen which exhibited immunological non-identity. The two variants showed trypsin binding activity, both were synthesized by hepatocytes, and both behaved as acute phase reactants.
The ubiquitous nature of alPi was evident from its presence in a wide variety of body fluids. Using an immunohistochemical stain, the inhibitor was shown to be normally present in the cytoplasm of hepatocytes, islet cells of pancreas and in some villous epithelial cells of the small intestine. The hepatocyte was shown to be the major source of serum αlPi. Alveolar macrophages, shown to contain αlPi histochemically in particular inflammatory states of the lung, synthesized minimal quantities.
The acute phase response of αlPi was investigated in four models of inflammation consisting of either a subcutaneous injection of celite or infection with one of three parasites: Nippostrongylus brasiliensis; Trichinella spiralis; and Trypanosoma congolense. In addition, studies have been initiated with other mouse acute phase reactants, namely, complement component C3, serum amyloid P (SAP) and serum amyloid A (SAA).
The induction of acute phase protein synthesis during inflammation was characterized by an increase in the number of hepatocytes staining for αlPi. During inflammation the level of hepatocyte staining was shown to correlate with the synthetic output of αlPi. The maximum staining activity for αlPi in hepatocytes preceded the peak increase in serum levels during inflammation. Moreover, there was a characteristic, progressive alteration in the distribution pattern of stained hepatocytes within the liver lobule. These results were consistent with an acute phase mediator perhaps originating from the site of inflammation, gaining access to the liver via the portal circulation causing an induction of acute phase protein synthesis.
The synthesis of an acute phase mediator (APM), probably interleukin 1 (ILl), by alveolar macrophages and the in vitro induction by APM of αlPi synthesis by hepatocytes has been demonstrated.
It was also shown that αlPi accumulated at the site of inflammation which may account for the apparent lack of increase in serum levels even though there was an increased hepatic output of alPi at that time.
Collectively these results demonstrate that in the mouse the induction of synthesis of αlPi during an acute response to inflammation is mediated by an acute phase mediator originating from macrophages at the site of inflammation.
The increased synthesis of αlPi has been shown in pivo by a measure of serum levels and immunohistochemical examination of liver tissue as well as in vitro by cultures of isolated hepatocytes.
These studies constitute a basic framework upon which mechanisms for the induction and control of synthesis of acute phase proteins can be further explored.
Keywords: Medical Sciences; Medical Sciences